Interferência do nível de ansiedade sobre a força relacional entre expressões faciais alegres e neutras e adjetivos positivos e negativos - Luana Martins Bittencourt (2023)
Anxiety disorders are highly prevalent in Brazil and affect approximately 3.6% of the global population. Research indicates that people with high levels of anxiety tend to have greater selective attention to threatening events and some studies have shown that neutral faces can be interpreted as threatening by these people. Studies in stimulus control area, which use face pictures as emotional stimuli, however, do not usually assess the presence or absence of anxiety disorders in their participants. The present study investigated whether the anxiety level could interfere with the relational strength between emotional stimuli (neutral and happy faces) and positive and negative adjectives. For this purpose, 133 unndergraduate students were divided into three groups (low, moderate and high anxiety) according the score obtained on the State-Trait Anxiety Inventory (STAI). Participants answered to STAI, short form of the Beck Depression Inventory, Semantic Differential Scale for happy and neutral faces, and performed a task in Implicit Relational Assessment Procedure (IRAP) in which they had to relate positive and negative adjectives with the faces. For IRAP analysis, 79 participants who attained the procedure criteria were selected. The results did not indicate difference between groups regarding to relational strength of stimuli in the IRAP, however, the group with with anxiety did not show a “single-trial-type-dominance-effect”.Furthermore, there was no IRAP Effect for trials involving neutral faces and negative adjectives. The results of Semantic Differential, however, seem to demonstrate that people with high anxiety tend to evaluate neutral faces as more negative, with a more pronounced effect for participants who also had severe depression.